TNF as a malaria candidate gene: Polymorphism-screening and family-based association analysis of mild malaria attack and parasitemia in Burkina Faso - Flori, L.; Delahaye, N.F.; Iraqi, F.A.; Hernández Valladares, M.; Fumoux, F.; Rihet, P. (Springer, 2005)
We have previously obtained strong evidence for linkage of mild malaria attack to the MHC region, with a peak close to the tumor necrosis factor (TNF) gene. We screened, for polymorphisms, the entire TNF gene in the same sample of 34 families comprising 197 individuals living in a Plasmodium falciparum endemic area and we found 17 polymorphisms. In a longitudinal study, we investigated whether the 11 most frequent and informative polymorphisms were associated with mild malaria attack and maximum parasitemia, which was the highest parasitemia in each individual over 2 years. Mild malaria attack and maximum parasitemia were positively correlated. Transmission disequilibrium tests showed nominal evidence for association between TNF-1031, TNF-308, TNF851 and TNF1304 polymorphisms, and mild malaria attack on the one hand, and between TNF-238, TNF851 and TNF1304 polymorphisms, and maximum parasitemia on the other hand. After accounting for multiple tests, we confirmed the association of TNF-238 with maximum parasitemia and the association of TNF1304 and TNF851 with maximum parasitemia and mild malaria attack. The association tests with mild malaria attack suggest a moderate effect of TNF-308 polymorphism. In conclusion, our study suggests that several TNF variants may be part of the genetic determinants for maximum parasitemia and/or mild malaria attack.